Hydatid Cyst in the Uterus of Young Lady - Yousuf, NA; Chowdhury, MAK; Ahmed, SU (Bangladesh Medical Journal, 2014)
Echinococcal disease remains a problem within some endemic areas. Echinococcal cysts usually involve the liver and lungs, but are extremely rare in the uterus. In this paper we report the rare case of a 27-year-old unmarried doctor presented with the complains of menorrhagia for 9 months and lump in lower abdomen for 6 months. Ultrasonography and MRI revealed a large multiloculated cystic lesion within the uterine cavity. Serological tests were positive for echinococcus. The patient was operated on; cysts were removed from uterine cavity. Antihelminthics were administered postoperatively and the patient was closely followed up for 9 months, without menorrhagia or recurrence of Echinococcal cyst. Although Echinococcal cysts are extremely rare in the uterus, it can be managed successfully. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18513 Bangladesh Medical Journal 2011 Vol.40(2): 58-60